COMPETENCE-BASED APPROACH TO PROFESSIONAL PHYSICAL CULTURE AND SPORTS EDUCATION - Atajanov Rasul Turganbaevich (Journals Park Publishing, 2022)
The article reveals the concept of professional competence, proposes the structure and content of professional competence of a specialist in physical culture and sports, provides general characteristics of a competency-based approach to professional education and determines their connection with the content of professional competence of specialists in physical culture and sports; the provisions of the competency-based approach are extrapolated to the sphere of professional physical culture and sports education.
Keywords: physical culture; competence-based approach; professional physical culture